Starting a Hul’q’umi’num’ kindergarten immersion program - Hall, Kelly M.A. (Electronic version published by Vancouver Island University, 2022)
Like many other First Nations languages in British Columbia, the ancestral language of the Quw’utsun people, my people, is on the verge of becoming extinct. The cultural genocide that was the residential school system continues to supress language and cultural practices within our homes and communities. If action is not taken immediately to revitalize the hul’q’umi’num’ language, Elders and their knowledge of language and Quw’utsun culture will be officially stolen, along with our cultural identity. As a result, I have become a language warrior, challenging systemic racism, and breaking a toxic cycle that was forced upon our people. I am learning the sacred language of my ancestors and I support hul’q’umi’num’ language revitalization efforts through a new language immersion program for the Quw'utsun people. The purpose of my Master of Education research was to explore what has been learned from First Nations language immersion programs in British Columbia. I was guided by the question: what does a new First Nations language immersion school need to know to support their early learners? I interviewed the Renee Sampson head teacher and Immersion Program Coordinator of ȽÁU, WELṈEW̱ Tribal School and myself, as the Kindergarten teacher of Quw'utsun Smuneem Elementary School. The findings from this research show that immersion programs are an essential part of language revitalization. Elders and language champions from the community have been drivers of First Nations language immersion programs in BC, however community support, strong educational leadership, and funding are essential to the success and sustainability of these programs. While community support is there, limited resources are available to fund language revitalization initiatives for all First Nations communities, risking language extinction as the few Elders that are fluent leave us for the ancestors. https://viurrspace.ca/bitstream/handle/10613/25979/Hall.pdf?sequence=3&isAllowed=y